Calories Count - Tips for Healthy Weight Management - Maurer, Jaclyn (College of Agriculture and Life Sciences, University of Arizona (Tucson, AZ), 2005)
4 pp. === Weight management is more than just cutting back on carbohydrate or fat. Controlling calories is key to achieving and maintaining a healthy weight. This publication reviews how calories count, not matter what type of diet you choose to follow.